PERLINDUNGAN HUKUM BAGI PIHAK PEMBELI DALAM PERJANJIAN PENGIKATAN JUAL BELI TERHADAP OBJEK TANAH MASIH DALAM PROSES PEMECAHAN DI DENPASAR UTARA - Dewi, Ni Nyoman Ayu Juliana; Darma Pratiwi, Agustina Ni Made (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Often there are delays in making a sale and purchase deed due to problems with the land object in the process of being resolved. The problem that will be discussed is how the legal protection and legal force of the Sale and Purchase Agreement for the buyer of land objects is still in the process of being resolved in North Denpasar. This research aims to determine the legal protection and legal strength of the Sale and Purchase Agreement (PPJB) for buyers of land objects still in the process of being resolved in North Denpasar. The type of research used is empirical legal research. The results of the research show that legal protection for buyers in the PPJB for land objects is still in the process of being resolved, namely that the PPJB is made before a Notary and has very strong proof, like authentic deed proof. The legal force of the PPJB for buyers of land objects is still in the process of being resolved, namely that the PPJB is made before a Notary as authentic evidence that can guarantee if a dispute occurs.